AN APPROXIMATE MODEL FOR DETERMINING THE RESISTANCE OF A HEMISPHERICAL GROUND ELECTRODE PLACED AT THE TOP OF A NONHOMOGENEOUS TRUNCATED CONE - Vučković, Dragan; Cvetković, Nenad; Stojanović, Miodrag; Tasić, Dragan (Journal of Energy Technology, 2025)
The procedure for analysis of a hemispherical ground electrode placed at the top of a hill is presented in the paper. The mountain is modelled as a truncated cone of finite height consisting of two homogeneous areas, each having different electrical characteristics. The applied approach is a combination of several recently proposed procedures. It includes the application of the Estimation method and the use of an approximate expression in closed form. The obtained results are validated and compared with those obtained using the COMSOL program package.